2017
DOI: 10.1002/ece3.2926
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal abundance and habitat use of bird species in and around Wondo Genet Forest, south‐central Ethiopia

Abstract: The habitat use and seasonal migratory pattern of birds in Ethiopia is less explored as compared to diversity studies. To this end, this study aimed at investigating the patterns of distribution related to seasonality and the effect of habitat characteristics (elevation, slope, and average vegetation height) on habitat use of birds of Wondo Genet Forest Patch. A stratified random sampling design was used to assess the avian fauna across the four dominant habitat types found in the study area: natural forest, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 19 publications
3
51
0
Order By: Relevance
“…The present study in Wabe fragmented forest, showed that bushland/shrub land support a considerable number of bird species (72%) and bird abundance (59.25%) as compared to riverine forest and human plantation habitats. This is in line with result of Desalgn & Subramanian, 4 Girma et al, 8 Aynalem & Bekele., 16 Bergner et al, 17 and Mengesha et al, 18 where high species diversity, richness and abundance of birds was observed in bushland habitat that might be associated with the vegetation composition that could create variations in food sources, nesting and protection opportunities based up on the bird's habitat preference and feeding habits.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present study in Wabe fragmented forest, showed that bushland/shrub land support a considerable number of bird species (72%) and bird abundance (59.25%) as compared to riverine forest and human plantation habitats. This is in line with result of Desalgn & Subramanian, 4 Girma et al, 8 Aynalem & Bekele., 16 Bergner et al, 17 and Mengesha et al, 18 where high species diversity, richness and abundance of birds was observed in bushland habitat that might be associated with the vegetation composition that could create variations in food sources, nesting and protection opportunities based up on the bird's habitat preference and feeding habits.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the presence of low species richness and abundance in the riverine forest might be associated with presence of homogeneous plant species which are selected only by few bird species. According to Girma et al, 8 a natural forest which is dominated by few tree species is not suitable to different bird species, because it does not fulfilled the feeding or nest building preferences of most species coupled with risk of predation and thus, it is preferred by few forest specialist bird species alone as they obtained sufficient cover and food requirements. In contrast, Mengesha & Bekele., 2 has reported highest avian species diversity was found in riverine woodland habitat in Alatish National Park, this variation might be associated with type of plant species found and feeding habit of the presented bird species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the variation in species dominance among different habitats could also be attributed to the presence food availability, suitable cover and nesting sites, adaptation or tolerance level of the species and the degree of the threats presented in the habitats. 8 But based on the relative abundance score, most of the occurred bird species were grouped under locally rare and uncommon species. Similar result is reported by Mengesha & Bekele 2 from Alatish National Park, North Gondar, Ethiopia, thus the occurrence of such species indicates there is a need of wildlife conservation prioritization in those habitats.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Therefore, the temporal and spatial species composition and abundance of birds in Ethiopia are mainly determined by vegetation structures used as food source, breeding sites and protection (shelter) resulting from climatic variations such as rainfall and temperature related to the topographical nature of a particular area. 7,8 Physical environments such elevation, slope and aspect determine the composition, structure and productivity of vegetation which influences the diversity, abundance and habitat use of many birds. 4 Birds are well known bio-indicators and they have a significant role in ecosystem functioning and balancing.…”
Section: Introductionmentioning
confidence: 99%